2016
DOI: 10.1073/pnas.1521599113
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast retrograde signal regulates flowering

Abstract: Light is a major environmental factor regulating flowering time, thus ensuring reproductive success of higher plants. In contrast to our detailed understanding of light quality and photoperiod mechanisms involved, the molecular basis underlying high light-promoted flowering remains elusive. Here we show that, in Arabidopsis, a chloroplast-derived signal is critical for high light-regulated flowering mediated by the FLOWERING LOCUS C (FLC). We also demonstrate that PTM, a PHD transcription factor involved in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…Whether 580 or not the involvement of GUN1 is also indicative of an involvement of retrograde signaling in 581 the regulation of flowering time, remains to be determined. Although a role of chloroplast 582 retrograde signals in the regulation of high light-induced early flowering was proposed and the 583 activation of FLOWERING LOCUS C was suggested as a possible mechanism (Feng et al, 2016), 584 the connection between retrograde signaling and high light-induced flowering was refuted by a 585 recent study (Page et al, 2017) and is also not supported by our data presented here 586 (Supplemental Fig. S6).…”
Section: Overexpression Of Gun1 Confers Early Flowering 443mentioning
confidence: 69%
See 1 more Smart Citation
“…Whether 580 or not the involvement of GUN1 is also indicative of an involvement of retrograde signaling in 581 the regulation of flowering time, remains to be determined. Although a role of chloroplast 582 retrograde signals in the regulation of high light-induced early flowering was proposed and the 583 activation of FLOWERING LOCUS C was suggested as a possible mechanism (Feng et al, 2016), 584 the connection between retrograde signaling and high light-induced flowering was refuted by a 585 recent study (Page et al, 2017) and is also not supported by our data presented here 586 (Supplemental Fig. S6).…”
Section: Overexpression Of Gun1 Confers Early Flowering 443mentioning
confidence: 69%
“…Although chloroplast retrograde signals have 458 been implicated in the promotion of flowering by high light (Feng et al, 2016), these results 459 were recently refuted by the demonstration that the suggested functional connection (the 460 transcription factor PTM) plays no role in retrograde signaling (Page et al, 2017). In an attempt 461 to resolve this controversy, we sought to examine whether or not GUN1 participates in high 462 light-induced early flowering.…”
Section: Overexpression Of Gun1 Confers Early Flowering 443mentioning
confidence: 99%
“…Many external and internal pathways influence flowering initiation including hormone, temperature, photoperiod, autonomous and age‐related pathways (He and Amasino, ). These different genetic pathways ultimately converge to regulate the key flowering repressor FLOWERING LOCUS C ( FLC ), a MADS‐box transcription factor and two main integrators of flowering FLOWERING LOCUS T ( FT ) and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 ( SOC1 ), which subsequently promote floral meristem identity genes (Lee et al ., ; Andrés and Coupland, ; Feng et al ., ). The multifactorial regulatory mechanisms controlling FLC expression are of special significance (He and Amasino, ).…”
Section: Introductionmentioning
confidence: 97%
“…The Zhang group recently revealed that the changes in flowering time in response to light intensity involve retrograde signaling from the chloroplast and the activities of FLOWERING LOCUS C (FLC), a MADS-box transcription factor that negatively regulates flowering, and PTM, a chloroplast envelope-bound plant homeodomain transcription factor (Feng et al, 2016). They found a clue to the interconnection between retrograde signaling and the regulation of flowering time from the observation that flc-3 and ptm mutants show altered flowering time, and their flowering is insensitive to high light irradiance, whereas wild-type plants respond to high light by flowering earlier.…”
mentioning
confidence: 99%
“…The existence of the N-PTM-FVE complex, as identified by the Zhang group, also explains how PTM, which has transcriptional activator activity, could repress FLC expression. PTM could act as a scaffold protein to form a high-molecular-weight multiprotein complex to affect the chromatin state of its target genes, thus causing either activation (e.g., ABI4) or repression (e.g., FLC) of these targets ( Figure 1) (Sun et al, 2011;Feng et al, 2016). Moreover, as the modification of chromatin structure is important in the regulation of flowering time by a subset of flowering time regulators (Bouche et al, 2016), it is likely that PTM has an additional target (or targets) other than FLC.…”
mentioning
confidence: 99%